KONTRIBUSI PEMIMPIN PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI PERGURUAN TINGGI - JUNAIDAH, JUNAIDAH (Universitas Islam Negeri Raden Intan Lampung, 2015)
Human resources are the key factors that determine the success of education. The leader is the person most responsible for all the processes of education and teaching that takes place in college. Leaders should strive for alumni of the college of education quality and deserves world amid global and modern. Education leaders not only act as a leader or a manager but also as educators, administrators, supervisors, and citizens should be able to move the campus towards quality education and cooperation among agencies. Today man is facing rapid change arising from the impact of science and liabilities . Especially if it is based on the assumption that all the problems that stem from the application of the concept and an education that stimulates and promotes the progression of science and technology uncontrollable. Islam also emerged among the various issues concerning the education crisis and other problems which urgently demands a solution in the form of the establishment of an educational system that is based on the concept of Islam. One solution is a management solution in education. Aside from the business world, as well as state management organizations have an important role to deliver educational progress. If countries pursue successful management development management education while pursuing successful human child development services through adequate education. The quality of success and education cannot be separated from the contribution of leaders in education itself. It therefore requires a leader who is wise, thoughtful, has a good personality and can direct subordinates to jointly contribute to realizing quality education. . Keywords: education leader, quality of education